COMPARISON OF LISINOPRIL AND BISOPROLOL INFLUENCES ON REGULATORY SYSTEMS OF THE ORGANISM IN BIOFEEDBACK SERIES IN HEALTHY VOLUNTEERS - Nazarenko, E. O.; Radchenko, A. O.; Belal, S. A. S.; Kulik, A. L.; Yabluchanskiy, N. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
In 15 conditionally healthy volunteers aged from 18 to 22 years influence of Lisinopril and Bisoprolol on the biofeedback in the loop of paced breathing under control of heart rate variability parameters was compared. Every volunteer underwent 3 everyday biofeedback series with 5 session in each with a 5 months gap between the series, adding oral drugs application to the 2nd and 3rd series. During the 2nd series biofeedback sessions was conducted one hour after oral application of 2,5 mg Lisinopril. During the 3rd series biofeedback sessions was conducted one hour after oral application of 2,5 mg Bisoprolol. In used protocol, it was found that Bisoprolol promotes earlier and more substantial optimization of regulatory systems in comparison with Lisinopril.